Manajemen Kelas Berbasis Permasalahan Siswa Dalam Pembelajaran Tematik di SDN 4 Grobogan - Yahmo, Sabar, Prof. Dr. Abdul Ngalim,M.M., M.Hum, Dr. Sabar Narimo, M.M., M.Pd (2016)
This study aimed to describe (1) Planning based classroom management issues in the thematic learning students at SDN 4 Grobogan (2) Implementation based classroom management issues in the thematic learning students at SDN 4 Grobogan. (3) Evaluation based class management issues in the thematic learning students at SDN 4 Grobogan. This study used a qualitative research method using descriptive analytical approach. This research is qualitative research using inductive data analysis. Analysis of data using an interactive model. The results showed that: (1) The teacher prepares learning media se possible start with an exploration technique, elaboration and collaboration. Planning is structured media preparation course has the goal to a better future. In addition to that the learning process becomes more conducive, is also expected student learning outcomes become more leverage. (2) It is known that the learning objectives that can be generated are learners become more character, active, disciplined, diligent, industrious, more attentive care and want to help each other in a problem-solving discussion in lessons ditematikkan; (3) The evaluation provides valuable contribution to the learners. More learners do not feel doing much about having been assembled into one part ditematikkan, making it easier to understand simple without losing the essence of these subjects.